PRO SQL SERVER 2008 ANALYSIS SERVICES - ZOUZELKOVA, Iveta (Journal of Technology and Information Education, 2011)
The main aim of this paper is to introduce Pro SQL Server 2008 Analysis Services written by Philo Janus and Guy Fouche to potential readers. The publication is intended for young database professionals interested in data mining and OLAP analysis. It consists of 14 chapters and two appendixes and is richly illustrated by screenshots of the application software. It contains many useful examples and advices from practice.
Keywords: Microsoft SQL Server 2008; Analysis Services; OLAP Analysis; MDX; Business Intelligence; Decision Support; Database